Herb gardening - Gray, Linda , 1948- (2009)
Herbs can form an exciting, versatile and handy part of any garden - be it an ornamental display, a kitchen corner, a container or just a windowsill. This practical book explains how to plant and harvest your own herbs. It describes some forty herbs with their history and photographs, as well as instructions on how and where to grow them.